Interação com o DNA e fototoxicidade de porfirinas tetracatiônicas de rutênio, areno e fosfina em células tumorais de ovário - Pereira, George Bueno Santana (Universidade Federal de São Carlos, 2025)
In this work, porphyrins derived from meso-tetra(4-pyridyl)porphyrin and meso-tetra(3-pyridyl)porphyrin were synthesized, along with their respective zinc(II) metalloporphyrin, coordinated to four peripheral ruthenium(II) complexes containing p-cymene and triphenylphosphine, forming a new class of compounds, called PRAP, and a mimetic compound (Mim). These compounds were characterized by spectroscopic techniques, mass spectrometry, elemental analysis and molar conductivity, as well as structural optimization calculations by DFT. Plasmid pUC19 and ct-DNA interactions were carried out, as well as an interaction with guanosine. The results suggest an interaction mechanism that initially involves an aggregation effect, followed by a possible covalent bond. Cellular assays showed that the compounds were not cytotoxic to the MRC-5 (non-tumor lung cancer) strain at concentrations below 50 μM. On the other hand, in the A2780 lineage (ovarian tumor), the tetra-cationic porphyrin showed high phototoxicity after irradiation, with an IC50 of approximately 0.07 μM for the free porphyrins and 0.30 μM for the zinc(II) metalloporphyrin. The H2P compound stood out for having the highest phototoxicity index. The morphological tests confirmed cell death by apoptosis and damage to the nucleus, corroborating the photobleaching data from the pUC19 plasmid. Finally, it was found that photodynamic treatment can affect the cell proliferation zone in tumor spheroids. These experiments show that the system evaluated has promising potential for interacting with DNA and acting as a photosensitizer.
DNA interaction and phototoxicity of tetracationic porphyrins of ruthenium, arene and phosphine in ovarian tumor cells
Keywords: Fototoxicidade; Interação com DNA; Porfirina; Complexo de rutênio(II); Phototoxicity; DNA Interaction; Porphyrin; Ruthenium(II) complex; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA::QUIMICA BIO-INORGANICA